Whatever happened to the Bismarckian welfare state? From labor shedding to employment-friendly reforms - Anton Hemerijck; Werner Eichhorst (Institute for the Study of Labor (IZA), 2009)
The paper challenges the widespread view that Bismarckian countries with a strong role of social insurance and labor market regulation are less successful than other employment regimes and hard to reforms. This has been true about a decade ago. But both the institutional set-up and the performance of Bismarckian countries have changed fundamentally over the last years. The paper summarizes major reform dynamics in Bismarckian welfare states which had adopted a strategy of labor shedding in the 1970s and 1980s to combat open unemployment. As this was associated with an increasing burden of non-wage labor costs, this triggered a sequence of more employment-oriented and more fundamental reforms that eventually helped overcome a low employment situation. The paper pursues the trajectory of reforms, shows the structural change in labor market performance and points out the achievements of past reforms, but also emphasizes the need for further action in terms of education and training, activation and employment opportunities for all working age people in these countries so that flexibility and security can be reconciled.
urn:nbn:de:101:1-20090330180
Keywords: J26; J68; 330; Bismarckian welfare states; social insurance; social policy; employment; labor market policies; Sozialstaat; Sozialreform; Arbeitsmarktpolitik; Reform; Arbeitsmarktflexibilisierung; Europa